Tinjauan Bibliometrik Terhadap Penelitian Pembelajaran Computer Graphic - Safitri Aprillia Putri (LP2M Sekolah Tinggi Seni Rupa dan Desain Visi Indonesia (STSRD VISI), 2022)
Computer Graphics is one of the fundamental courses in the field of visual communication design. This course studies the technicalities of organizing visual communication media with the help of a computer. This research was conducted to review research related to computer graphics education during 2011-2021. The contribution of this research is as a basis for a different intellectual framework by identifying the productivity of publications and topics. For this reason, bibliometric techniques were used to analyze 645 documents published from 2011-2021 based on the Scopus database. The results of the Scopus data analysis revealed that from 2011 to 2021 the number of publications related to computer graphic education experienced a dynamic development trend.